2007
DOI: 10.1101/lm.781507
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional expression of brain-derived neurotrophic factor following olfactory fear learning

Abstract: We examined brain-derived neurotrophic factor (BDNF) mRNA expression across the olfactory system following fear conditioning. Mice received 10 pairings of odor with footshock or equivalent unpaired odors and shocks. We found increased BDNF mRNA in animals receiving paired footshocks in the multiple regions examined including the posterior piriform cortex (PPC) and basolateral amygdala (BLA). This was in contrast to the unpaired and odor-alone treatments, where BDNF mRNA was increased in the olfactory bulb (OB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
5
37
0
Order By: Relevance
“…In turn, the amygdala sends direct projections back to the piriform cortex (Majak et al 2004). Moreover, the BLA plays a major role in the acquisition, consolidation, and retention of olfactory fear conditioning (Cousens and Otto 1998;Rosenkranz and Grace 2002;Kilpatrick and Cahill 2003;Sevelinges et al 2004Sevelinges et al , 2007Walker et al 2005;Jones et al 2007), thus extending previous observations with auditory and visual CSs to include odor cues. Recent studies also suggest that the posterior piriform cortex (pPCx) may play a critical role in this associative learning (Sevelinges et al 2004(Sevelinges et al , 2008Jones et al 2007).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…In turn, the amygdala sends direct projections back to the piriform cortex (Majak et al 2004). Moreover, the BLA plays a major role in the acquisition, consolidation, and retention of olfactory fear conditioning (Cousens and Otto 1998;Rosenkranz and Grace 2002;Kilpatrick and Cahill 2003;Sevelinges et al 2004Sevelinges et al , 2007Walker et al 2005;Jones et al 2007), thus extending previous observations with auditory and visual CSs to include odor cues. Recent studies also suggest that the posterior piriform cortex (pPCx) may play a critical role in this associative learning (Sevelinges et al 2004(Sevelinges et al , 2008Jones et al 2007).…”
supporting
confidence: 55%
“…Moreover, the BLA plays a major role in the acquisition, consolidation, and retention of olfactory fear conditioning (Cousens and Otto 1998;Rosenkranz and Grace 2002;Kilpatrick and Cahill 2003;Sevelinges et al 2004Sevelinges et al , 2007Walker et al 2005;Jones et al 2007), thus extending previous observations with auditory and visual CSs to include odor cues. Recent studies also suggest that the posterior piriform cortex (pPCx) may play a critical role in this associative learning (Sevelinges et al 2004(Sevelinges et al , 2008Jones et al 2007). Therefore, the olfactory system constitutes a particularly relevant model for studying the relative contribution of sensory cortices and amygdalar nuclei to odor fear learning.…”
mentioning
confidence: 65%
“…4). This remarkable degree of plasticity within the olfactory and limbic systems adds to previous evidence that olfactory perceptual learning can modify both piriform and orbitofrontal activity patterns (Schoenbaum et al, 1999; Sevelinges et al, 2004;Kadohisa and Wilson, 2006;Li et al, 2006;Jones et al, 2007;Roesch et al, 2007;Li et al, 2008;Chapuis et al, 2009), underscoring the idea that odor information content can be dynamically updated in these regions. We also found that category learning-related changes within PPC, pOFC, and INS were specific to the olfactory modality.…”
Section: Discussionmentioning
confidence: 58%
“…BDNF signaling through its primary receptor TrkB has also been shown to play a significant role in downstream effects underlying learning (36)(37)(38)(39)(40). Previous data from our laboratory have shown increased BDNF transcription and translation in the OB following olfactory fear conditioning (41). Furthermore, OSNs within the MOE express the BDNF receptor TrkB (42).…”
Section: Discussionmentioning
confidence: 72%